Discovery of formicomyces microglobosus gen. et sp. nov. strengthens the hypothesis of independent evolution of ant-associated fungi in Trichomeriaceae - Siedlecki, Igor; Piątek, Marcin; Majchrowska, Maria; Okrasińska, Alicja; Owczarek-Kościelniak, Magdalena; Pawłowska, Julia (Fungal biology, 2023)
Different groups of fungi have been reported to interact with ants. Recent studies have shown that fungi of the order Chaetothyriales are important components of ant-fungus networks, including members of the family Trichomeriaceae, which is particularly rich in fungi isolated from carton ants nests. One of the still understudied ant-related environments are ants' infrabuccal pockets and pellets, which often contain fungal matter. The aim of this work was to determine the systematic and phylogenetic position of two slow growing strains of Trichomeriaceae isolated from infrabuccal pellets of Formica polyctena ants. Molecular analyses based on maximum likelihood and bayesian inference, using sequences of two ribosomal DNA markers: ITS and LSU have shown that the isolated strains form a monophyletic clade within the family Trichomeriaceae, sister to a clade formed by representatives of the genus Trichomerium. Morphological analyses additionally justified distinctiveness of the isolated strains, which have different morphology of conidia and conidiophores than Trichomerium representatives. Therefore, our results show that the isolated strains represent a new species within a not yet described fungal genus. Due to the strains’ isolation source and their close relatedness to a fungal strain isolated from a carton nest of Lasius fuliginosus, we propose a name Formicomyces microglobosus Siedlecki & Piątek for this fungus. While our discovery strengthens a hypothesis of the multiple, independent evolution of ant-associated fungi in the family Trichomeriaceae, the ecology of F. microglobosus still remains to be characterized.
Online veröffentlicht: 24. Oktober 2023
Gesehen am 14.05.2024